A perspective on decarbonizing whiskey using renewable gaseous biofuel in a circular bioeconomy process. (10th May 2020) - Kang, Xihui; Lin, Richen; O'Shea, Richard; Deng, Chen; Li, Lianhua; Sun, Yongming; Murphy, Jerry D.
Abstract: Low-carbon circular economy strategies within the whiskey industry necessitate minimal use of fossil-based energy including heat and electricity. Renewable energy generated from process by-products such as draff and pot ale offers opportunities for circular bioeconomy systems. However, such a system is yet to be defined and assessed in detail. In this study, biological valorization (dark hydrogen fermentation and anaerobic digestion) of whiskey by-products was comparatively evaluated in terms of fundamental principles and thermodynamics of biochemical reactions. Four scenarios based on a whiskey plant size of 2 million L/a were evaluated to determine the potential energy recovery (in the form of electricity and heat) and CO2 emissions reduction. The recommended scenario with anaerobic digestion of pretreated by-products resulted in a biogas production of 1.72 million m 3 (containing 1.03 million m 3 biomethane, corresponding to an energy yield of 10, 300 MWh). If the produced biogas is used for producing heat and electricity in a combined heat and power system, 446% of the annual electricity demand (740 MWe h) and 25% of the heat demand (4, 230 MWth h) of the traditional distillery can be covered, leading to a reduction in energy related CO2 emissions of 61% from whiskey production (2, 300 ton CO2 ). Preliminary economic analysis shows that the proposed system has an annual net income of €741, 176 with a payback period of 3.94 years. Net present value of the system is €4, 933, 456 with a discounted payback period of 4.77 years. Future research on a detailed techno-economic feasibility and life cycle assessment of such a system should be investigated before practical implementation. Graphical abstract: Image 1 Highlights: Anaerobic digestion with integrated pretreatment is proposed to valorize by-products. Biogas can satisfy 446% of electricity and 25% of thermal energy in a distillery. The proposed system has a potential to reduce distillery CO2 emissions by 61%. A techno-economic analysis of the proposed system showed a payback period of 4 years.